2013
DOI: 10.1016/j.ajhg.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Large Sample Size, Wide Variant Spectrum, and Advanced Machine-Learning Technique Boost Risk Prediction for Inflammatory Bowel Disease

Abstract: We performed risk assessment for Crohn's disease (CD) and ulcerative colitis (UC), the two common forms of inflammatory bowel disease (IBD), by using data from the International IBD Genetics Consortium's Immunochip project. This data set contains ~17,000 CD cases, ~13,000 UC cases, and ~22,000 controls from 15 European countries typed on the Immunochip. This custom chip provides a more comprehensive catalog of the most promising candidate variants by picking up the remaining common variants and certain rare va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 20 publications
3
171
1
Order By: Relevance
“…[215] In fact, an extensive GWAS of inflammatory bowel disease recently showed that including hundreds of variants with suggestive, but not genome-wide significant associations, improved substantially risk prediction compared to models limited to GWAS findings. [216] Accordingly, it can be expected that incorporating a large number of genetic variants from genome-wide scans can further improve risk-prediction models, particularly if based on large sample sizes. [216220]…”
Section: Impact Of Genetic Loci On Treatmentmentioning
confidence: 99%
“…[215] In fact, an extensive GWAS of inflammatory bowel disease recently showed that including hundreds of variants with suggestive, but not genome-wide significant associations, improved substantially risk prediction compared to models limited to GWAS findings. [216] Accordingly, it can be expected that incorporating a large number of genetic variants from genome-wide scans can further improve risk-prediction models, particularly if based on large sample sizes. [216220]…”
Section: Impact Of Genetic Loci On Treatmentmentioning
confidence: 99%
“…Recently an assay, called ImmunoChip, has been developed including 200,000 single nucleotide polymorphisms (SNPs) relevant to IBD and other immune-mediated diseases 22 . Studies of SNPs and insertion-deletion polymorphisms identified a total of 163 loci associated with IBD and revealed important pathways involved in IBD pathogenesis such as host-microbe interactions and autophagy 5,21 .…”
Section: A Characterization Of the Ibd Genomementioning
confidence: 99%
“…Only recently have similar approaches begun being applied to human disease, with notable success in CD (discussed below), T1D, and inflammatory bowel disease [13,22,23 ,24-26], and to a lesser extent in other diseases such as multiple sclerosis [27]. Commonly used models include L1-penalized logistic regression [24,26], kernel support-vector machines (SVM) [13], L1-penalized SVM [11 ,12 ,22], and variants of Bayesian models employing a genetic relatedness matrix (GRM), including linear [23 ,28] and probit [15] regression. Regardless of the model used, the same principle applies to all: each method represents a mathematical mapping from the SNP data (either a large subset of SNPs or all SNPs) to the phenotype, which is then applied to new SNP data to produce predicted phenotypes, typically in terms of a continuous genomic risk score (GRS).…”
Section: Methods and Relative Performance For Genomic Predictionmentioning
confidence: 99%